Can Lower Levels of Classroom Victimization be harmful? Healthy Context Paradox Among Chinese Adolescents - Xiong, Yuke (Journal of interpersonal violence, 2023)
The healthy context paradox is defined as the phenomenon that victims’ psychological adjustment worsens in a context with a lower rate of victimization. The unexpected pattern was primarily confirmed in children and adolescents from western societies, and it is unclear whether classroom-level victimization could moderate the link between peer victimization and psychological adjustment in the Chinese cultural context, where Confucian philosophies and collectivism are highly valued. Furthermore, most existing research used a single method to assess peer victimization. The current study attempted to examine classroom-level peer victimization as a moderator in the association between individual-level peer victimization and depression, self-esteem, and well-being among 2613 Chinese seventh graders (1237 girls, Mage = 13.00±.61) from 47 classrooms (Mclassroom size = 55.60, range from 45 to 65) using both self-reported and peer-reported information on peer victimization. At the individual level, the results revealed that both self- and peer-reported victimization were positively related to depression and negatively related to self-esteem and well-being. Most importantly, consistent with past findings documenting the healthy context paradox, self-reported victimized youth experienced a higher level of depression and lower level of self-esteem and well-being in classrooms where the overall level of victimization was relatively low. However, the healthy context paradox was not replicated in the nominated data of peer victimization. These results confirmed the healthy context paradox in Chinese culture to some extent. The findings emphasize the importance of measuring peer victimization from multiple sources and suggest there is a need for additional support to victimized middle school students where the classroom context was relatively healthy.